THE TRANSLATION TECHNIQUES USED IN THE BILINGUAL DESTINATION MAP “PETA WISATA JAWA TENGAH” TRANSLATED INTO “CENRAL JAVA TOURIST MAP” - Mayantina Arafanti; Rahmanti Asmarani (Universitas PGRI Semarang, 2016)
This study aims to find the translation techniques used by the translator in translating sentences of the bilingual destination map. The researchers used descriptive qualitative method to describe the translation techniques applied in the bilingual destination map “Peta Wisata Jawa Tengah” which is translated into “Central Java Tourist Map”. This study starts by finding the problem, collecting data, classifying data, analyzing data, and drawing the conclusion. The mostly used in translation techniques is literal translation technique to make the translation work clear for the tourists domestic even international. This technique is used when the target language (TL) is applied through the sentence without observing the differences of context or meaning in the source language (SL), whereas the discursive creation and description are rarely used.